Reproductive success of a marine teleost was correlated with proactive and reactive stress‐coping styles. Issue 3 (21st March 2019) - Ibarra‐Zatarain, Zohar; Parati, Katia; Cenadelli, Silvia; Duncan, Neil
Abstract : The present study investigated the relationship between reproductive success and stress‐coping styles in gilthead seabream Sparus aurata in captivity. To characterise stress‐coping styles, a total of 22 breeders were submitted to three different individual‐based tests, one group‐based test and post‐handling glucocorticoid quantification. To assess spawning participation, a microsatellite analysis was performed on a total of 2698 larvae, which allowed each offspring to be assigned unambiguously to a single parental couple. Overall, S. aurata showed defined proactive and reactive behavioural traits. Proactive breeders exhibited higher levels of activity and risk taking and lower glucocorticoid blood levels than reactive breeders. The stress‐coping style traits were consistent over time and context (different tests). Breeders that contributed to a higher number of progeny exhibited proactive behaviours, while those showing low progeny contribution exhibited reactive behaviour. Therefore, breeders with a high proportion of progeny (> 20%) had significantly higher activity and risk taking and lower cortisol than breeders with low progeny contribution (< 20%). In addition, males were more proactive than females and males exhibited significantly higher activity, risk taking and lower cortisol than females. This study is the first to establish in S. aurata breeders: (a) a relationship between stress‐coping styles and spawning success; (b) a relationship between stress‐coping styles and gender; and (c) the existence of proactive and reactive traits at the adult stage.